Functional analysis of nuclear receptor HR96 gene in Bombyx mori exposed to phoxim. Issue 2 (25th April 2022) - Liu, Tianrun; Xu, Xinyue; An, Fudong; Zhu, Weihao; Luo, Dongling; Liu, Shuo; Wei, Guoqing; Wang, Lei
Abstract: The nuclear receptor (NRs) gene family functions as ligand‐dependent transcription factors in a variety of animals, which participates in a variety of biological processes, such as cell differentiation, metabolic regulation, reproduction, development, insect metamorphosis. In this study, a nuclear receptor HR96 gene in silkworm Bombyx mori ( BmHR96 ) was identified, and the responses of BmHR96 gene to 20‐hydroxyecdysone (20E), three insecticides, and two disinfectants were analyzed and its function in phoxim exposure was explored.  Quantitative real‐time polymerase chain reaction indicated that the expression of BmHR96 mRNA was the highest in ovary of 5th instar Day 3 silkworm larvae and in silk gland of the wandering stage. The expression patterns of BmHR96 gene in ovary, head, testis, and midgut of different stages were different. After injecting 20E into B. mori, the expression of BmHR96 mRNA had no significant difference compared with control. Three insecticides and two disinfectants were used to treat B. mori, respectively, and it was found that they had different influence patterns on the expression level of BmHR96 . siRNA of BmHR96 was injected into silkworm larvae and the expression of BmHR96 was decreased significantly after injecting 72 h. After silencing of BmHR96, B. mori was fed with phoxim‐treated leaves. The results showed that the mortality of B. mori after silencing of BmHR96 was significantly higher than the control. Our results indicated that HR96 plays an important role in regulating the stress response of phoxim. Abstract : Expression profiles of BmHR96 induced by phoxim and the mortality of silkworm treated with phoxim after BmHR96 knocking down. Highlights: BmHR96 mRNA was not significantly induced by 20E in B. mori . The expression patterns of BmHR96 were different when silkworm treated with different pesticides or disinfectants. When silkworm feeding with phoxim‐treatment leaves after silencing of BmHR96, the mortality of B. mori was significantly higher than the control.